Relationship Between the Role of Extension Workers and the Implementation of Farmer Group Functions : Case Study in Limumir Village, Bula District - Yanti, Nefi; Damanik , Inta P. N .; Far Far , Risyart A. (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
Farmer groups serve as a crucial medium for enhancing farmers’ skills, while agricultural extension officers play an important role in assisting and facilitating farmers to become more productive and competitive. This study aimed to (1) analyse the significant role of farmer groups in supporting horticultural farmers in Limumir village, (2) examine the role of agricultural extension officers in horticultural farmer groups, and (3) analyse the correlation between the role of agricultural extension officers and the function of farmer groups. This study employed both quantitative and qualitative approaches. Research population consisted of 68 members of horticultural farmer groups in Limumir village, from three farmer groups: Maju Bersama, Suka Maju, and Fajar Tani. Data were collected through observations, interviews, questionnaires. The data were then analysed using Spearman's Rank Correlation test to examine the correlation between the role of agricultural extension officers and the function of farmer groups. The results revealed that the role of agricultural extension officers as facilitators and assistants to farmers had a significant impact on the efficiency of farmer groups in learning as collaboration aspects. Farmer groups with intensive supervision from agricultural extension officers showed increased technology adoption, better access to the market, and higher productivity. However, the role of agricultural extension officers in marketing was low, so a number of farmers still face challenges in accessing broader markets.